Pengakuan dan Pengukuran Instrumen Bebas Bunga Serta Peran Dewan Pengawas Syariah dalam Pelaporan Keuangan: Perbedaan Bank Syariah dan Konvensional - Sarimastini, Agustina; Hamzani, Umiaty; Fahmi, Muhammad; Helmi, Syarif Muhammad; Dosinta, Nina Febriana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the differences in the recognition and measurement of interest-free instruments and the role of the Sharia Supervisory Board in financial reporting between Islamic and conventional banks. The method used was a systematic literature review (SLR) of articles comparing the financial systems of the two types of banks. The results of the study indicate that Islamic banks use Sharia contract principles such as murabahah, mudharabah, and ijarah as a substitute for interest, while conventional banks rely on interest-based income. The role of the Sharia Supervisory Board (SSB) has proven significant in maintaining Sharia compliance, increasing accountability, and transparency in Islamic banks' financial reports. This study provides important insights for regulators, academics, and practitioners in developing Sharia-based financial reporting in Indonesia.